Exploring the 12C(18O, 16O)14C two-neutron transfer reaction at energies far above the Coulomb barrier. (March 2015) - Carbone, D; Cappuzzello, F; Agodi, C; Bonaccorso, A; Bondì, M; Cavallaro, M; Cunsolo, A; De Napoli, M; Foti, A; Linares, R; Lubian, J
Abstract: The 12 C( 18 O, 16 O) 14 C two-neutron transfer reaction has been studied at an incident energy of 275 MeV and the ejectiles have been momentum analysed at forward angles by the MAGNEX spectrometer. The identification of the 16 O ejectiles was obtained by combining a standard Δ E-E technique with the simultaneous measurement of the angle and the position at the focal plane. The 14 C excitation energy spectra have been obtained and several known bound and resonant states of the residual nuclei have been identified. The results have been compared to a previous measurement of the same reaction at 84 MeV incident energy.